2018
DOI: 10.1039/c7cp06211g
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-specific detection in the UV photodissociation of the propargyl radical by chirped-pulse mm-wave spectroscopy in a pulsed quasi-uniform flow

Abstract: Isomer-specific detection and product branching fractions in the UV photodissociation of the propargyl radical is achieved through the use of chirped-pulse Fourier-transform mm-wave spectroscopy in a pulsed quasi-uniform flow (CPUF). Propargyl radicals are produced in the 193 nm photodissociation of 1,2-butadiene. Absorption of a second photon leads to H atom elimination giving three possible CH isomers: singlets cyclopropenylidene (c-CH) and propadienylidene (l-CH), and triplet propargylene (HCCCH). The singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…The mm-wave spectrum allows discrimination between (and at least approximate quantitation of) the various C3H2 isomers and confirms that H + 3 HCCCH products constitute ~80% of the total dissociation yield. 227 Photofragmentation studies involving the various C3H2 isomers are still rare. Propargylene (HCCCH) has a triplet ground state.…”
Section: 3mentioning
confidence: 99%
“…The mm-wave spectrum allows discrimination between (and at least approximate quantitation of) the various C3H2 isomers and confirms that H + 3 HCCCH products constitute ~80% of the total dissociation yield. 227 Photofragmentation studies involving the various C3H2 isomers are still rare. Propargylene (HCCCH) has a triplet ground state.…”
Section: 3mentioning
confidence: 99%
“…For example, simultaneous broadband detection of isomerizing molecules enables "dynamic rotational spectroscopy" (31,41). The relative transition intensities in CP experiments can be converted to branching ratios of multiple reaction products for chemical kinetics studies (42)(43)(44)(45). A recent study of 193-nm photolysis of vinyl cyanide (VCN) in a roomtemperature reactor revealed a new pathway to HCCCN by measuring the time evolution of the vibrational-level population distribution (VPD) in a CPmmW spectrum (43).…”
mentioning
confidence: 99%
“…Subsequent disappearance of l-C3H2 and appearance of intense c-C3H2 (after 70 µs) is ascribed to H-atom catalyzed isomerization in the high-density region of the flow as discussed previously. 183 Singlet propargylene is also a possible product isomer, but we cannot detect it owing to its negligible dipole moment. We would expect this to undergo H catalyzed isomerization to c-C3H2, which would appear at later times, just as we have shown for the triplet propargylene and l-C3H2.…”
Section: This Is Much As What We Have Seen For Hcl Elimination In CL + Butene Reactions For Which Onlymentioning
confidence: 81%
“…The propargyl chloride is seeded at 1% in helium and expanded from a Laval nozzle forming a quasi-uniform flow at a total density of ~10 16 cm -3 and a temperature of products, and the isomer-specific branching is the subject of studies reported elsewhere. 183 The photoproducts are internally cooled in the flow, after which they are excited by π/2 pulses of mmwave radiation tuned to known transitions of C3H2 isomers at time intervals of 10 µs. After each mm-wave pulse, the free induction decay of the excited molecules is acquired and accumulated in the time domain, then Fourier-transformed to give the rotational spectrum from which branching is determined as described previously.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation